2013
DOI: 10.1603/en13032
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Localization ofRickettsia spin Mealybug

Abstract: Mealybug, Phenacoccus solenopsis Tinsley, is a sap-sucking hemipteran insect. It is an agricultural pest that is now widely distributed in India. In this study we report the presence of Rickettsia from P. solenopsis. We constructed a 16S rRNA gene library to study the bacterial diversity associated with this insect and we found that all the clones from the library were only of Candidatus Tremblaya phenacola. This study also highlights that the normal protocol adopted to study the bacterial diversity from envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
(23 reference statements)
1
10
0
Order By: Relevance
“…Genus specific primers have been reported to be more sensitive for the detection of less populated bacterium [21]. We observed an amplification product of 632 bp which was in accordance with the expected size of 16S rRNA gene with genus specific primers of Wolbachia [22] in all three populations. Similarity search result using BLAST algorithm (search was performed against nucleotide sequence nr/nt, scoring parameter; match/mismatch scores were 1/-2 and gap cost set as linear) in NCBI showed that sequence of this product was 99 % identical to previously deposited sequences of Wolbachia from other insects in the GenBank.…”
Section: Detection and Reconfirmation Of Wolbachia In T Palmisupporting
confidence: 85%
See 2 more Smart Citations
“…Genus specific primers have been reported to be more sensitive for the detection of less populated bacterium [21]. We observed an amplification product of 632 bp which was in accordance with the expected size of 16S rRNA gene with genus specific primers of Wolbachia [22] in all three populations. Similarity search result using BLAST algorithm (search was performed against nucleotide sequence nr/nt, scoring parameter; match/mismatch scores were 1/-2 and gap cost set as linear) in NCBI showed that sequence of this product was 99 % identical to previously deposited sequences of Wolbachia from other insects in the GenBank.…”
Section: Detection and Reconfirmation Of Wolbachia In T Palmisupporting
confidence: 85%
“…Genomic DNA samples of three populations of well identified T. palmi were subjected to PCR for detection of Wolbachia with genus specific 16S rRNA gene primers. Conventionally, a 16S rRNA gene library is made to study bacterial endosymbiont population, but this technique does not detect bacterial endosymbionts which are rare [22]. Genus specific primers have been reported to be more sensitive for the detection of less populated bacterium [21].…”
Section: Detection and Reconfirmation Of Wolbachia In T Palmimentioning
confidence: 99%
See 1 more Smart Citation
“…These discrepancies are possibly due to the use of different probes in each study. The Wolbachia and Rickettsia that were found in high relative abundance in C. floridensis and M. mangiferae , respectively, are likely secondary symbionts of these species, as they often are in other sternorrhynchan families (e.g., Chiel et al., ; Singh, Kumar, Thomas, Ramamurthy, & Rajagopal, ; Zytynska & Weisser, ). Among the many bacterial OTUs that were amplified from our samples, there were also sequences of Uzinura diaspidicola , Buchnera aphidicola , Tremblya princeps and Moranella endobia (Appendix ).…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of obligate nutritional symbiosis has been highly dynamic in mealybugs, with some groups harboring Tremblaya alone, others harboring Tremblaya and Moranella, and others harboring an as yet unnamed obligate symbiont in the Bacteroidetes [35]. Mealybug bacterial facultative symbionts have received much less attention, although infections with acetic acid-producing bacteria [21], Spiroplasma [24], and Rickettsia [63] have been documented. Little is known about fungal associates of mealybugs although Buchner [6] reported yeast-like symbionts in the mealybug Rastrococcus iceryoides.…”
Section: Introductionmentioning
confidence: 99%